Mode II interlaminar failure mechanisms in carbon fibre / PEEK and carbon fibre / epoxy composites - Rozli Zulkifli,; Cantwell, Wesley J.; Matt Blyton, (1999)
The mode II interlaminar fracture properties of two high performance composites have been examined in detail. The failure mechanisms occurring in these materials are investigated using the double end-notched flexure (DENF) geometry. Tests have been undertaken at crosshead displacement rates between 0.1 mm/minute and 3m/s and the failure mechanisms investigated in the scanning electron microscope. Detail studies of the crack tip regions in the DENF specimens showed that the amount and nature of damage depended strongly on the rate at which the specimen was deformed. At low loading rates, the crack tip damage zone in carbon fibre reinforced PEEK was very large extending on planes above and below that of the starter defect. At high rates of loading, damage was confined to the resin-rich region immediate to the crack tip. Similar observations were made in the carbon fibre/epoxy composite where large shear cracks were evident at low - rates of loading and an array of microcracks at high rates